4D‐Printed Self‐Shaping Material Systems: Bio‐Inspired Motion Mechanisms: Computational Design and Material Programming of Self‐Adjusting 4D‐Printed Wearable Systems (Adv. Sci. 13/2021). Issue 13 (7th July 2021) - Cheng, Tiffany; Thielen, Marc; Poppinga, Simon; Tahouni, Yasaman; Wood, Dylan; Steinberg, Thorsten; Menges, Achim; Speck, Thomas
Abstract : The technical transfer of plant movement principles offers vast potentials for the development of novel, autonomously actuated structures. In article number 2100411 by Tiffany Cheng, Achim Menges, and co‐workers introduces a design and material programming approach for 4D‐printing adaptive material systems through a case study of biomimetic design. Based on the force generating mechanism of the air potato ( Dioscorea bulbifera ), the authors demonstrate the manufacture of a self‐tightening orthotic device.